Biomechanical evaluation of freestyle swimming - Rouard, A. (World book of swimming: From science to performance, 2012)
The swimming velocity resulted from the combination of the propulsivc and drag forces. The biomechanics evaluation was strongly improved during the 30 last years. Results underlined the main contribution of the hand in the swimming propulsion. The in-sweep-pull phase appeared the most important phase of the stroke either for kinematics (hand, elbow paths, velocity and acceleration) or kinetics (forces) and muscular activations. Fatigue state lead to a decrease of the in-sweep efficiency, the swimmer not be able to maintain the forces, muscles contributions and path during this constraining phase. The strength capacity seems to be a necessary but not sufficicnt parameter of the performance which is more related to the swimming force and power. Kinematics, kinetics and electromygraphic measurements confirmed the complemenlarity of the dry land and the water training process, the first allowing control of different parameters (muscles, imbalance, velocity, load), the second one more reproducing the race condition.